Study of the dynamics of model actuator using video - Седач, В. В.; Shireen, Muhamad (Eastern-European Journal of Enterprise Technologies, 2012)
The results of theoretical and experimental studies of the type actuator are given. Refined mathematical model allows to take into account the processes of change undulating pressure in the cylinder. There are approved original method of experimental study of the dynamics of the drive with the use of video recording and subsequent data processing video files with special programs for plotting to transient displacement, velocity and acceleration of the output link